Expression Profile of Sphingosine Kinase 1 Isoforms in Human Cancer Tissues and Cells: Importance and Clinical Relevance of the Neglected 1b-Isoform. (7th December 2022) - Chen, Hongjie; Haddadi, Nahal; Zhu, Xiaofeng; Hatoum, Diana; Chen, Size; Nassif, Najah T.; Lin, Yiguang; McGowan, Eileen M.
Abstract : Background .Overexpression of sphingosine kinase 1 (SphK1) is casually associated with many types of cancer, and inhibitors of SphK1 sensitize tumors to chemotherapy. SphK1 is expressed as two major isoforms, SphK1a and SphK1b. To date, no information has been reported on the SphK1 isoform expression profile and its clinical relevance. Objective . The objective is to examine the expression profile of the SphK1a and SPhK1b isoforms in human cancer and noncancer tissues and cell lines and explore their clinical relevance. Methods . We used PCR to qualitatively examine the expression profile of these two isoforms in breast, liver, and prostate cancer tissues plus paired adjacent tissues and in 11 cancer and normal cell lines (breast, cervical, bone, prostate, colon, brain, mesothelioma tumor and benign, and human kidney cells). Results . We found that SphK1a was ubiquitously expressed in all cancer cells and tissues tested; in contrast, SphK1b was only expressed in selective cell types in breast, prostate, and lung cancer. Conclusions . Our data suggest that SphK1a is important for generic SphK1/S1P functions, and SphK1b mediates specialized and/or unique pathways in a specific type of tissue and could be a biomarker for cancer. This discovery is important for future SphK1-related cancer research and may have clinical implications in drug development associated with SphK1-directed cancer treatment.